ANALISIS PENGARUH ECONOMIC VALUE ADDED DAN KINERJA KEUANGAN BERBASIS AKUNTANSI TERHADAP ABNORMAL RETURNS SAHAM PADA PERUSAHAAN KATEGORI KOMPAS 100 BURSA EFEK INDONESIA - Ricky Talumantak (LPPM Universitas Asa Indonesia, 2016)
This research is aimed to measure the influence of Economic Value Added (EVA) as an alternative to measure the financial performance of the value based company compsare with financial performance f the accounting based company. The performance of the 100 companies preferred stock by Kompas were analyzed by using multiple regression anaylisis,for the period of 2011-2013 by Cash Flow from Operation (CFO, Earnings Before Interest and Tax (EBIT) against abnormal stock returns. It is measured by incremental information content to confirm the influence among the EVA that consist of Accrual, CFO, Capital Charge against abnormal stock returns. The finding of this research are categorized as follows that EBIT is stronger to influence the abnormal return than EVA. The operating accrual dan operating cash flow (CFO) has the incremental information content inbfluewnced the abnormal stick returns than EVA of the non accountinbg cost of capital based company.